Adhesive Films from Dopamine‐Functionalized Polydimethylsiloxane Polymer Conetworks. Issue 8 (19th April 2023) - Mugemana, Clément; Mertz, Grégory; Grysan, Patrick; Dieden, Reiner; Ruch, David
Abstract : Front Cover : In article 2200456 by Clément Mugemana and co‐workers, adhesive films prepared from polydopamine‐functionalized polydimethylsiloxane polymer co‐networks with tunable stiffness and nanoscale phase‐separated morphologies are presented.